Design and evaluation of synthetic bacterial consortia for optimized phenanthrene degradation through the integration of genomics and shotgun proteomics - Macchi, Marianela (2021)
Two synthetic bacterial consortia (SC) composed of bacterial strains Sphingobium sp. (AM), Klebsiella aerogenes (B), Pseudomonas sp. (Bc-h and T), Burkholderia sp. (Bk) and Inquilinus limosus (Inq) isolated from a natural phenanthrene (PHN)-degrading consortium (CON) were developed and evaluated as an alternative approach to PHN biodegradation in bioremediation processes. A metabolic network showing the potential role of strains was reconstructed by in silico study of the six genomes and classification of dioxygenase enzymes using RHObase and AromaDeg databases. Network analysis suggested that AM and Bk were responsible for PHN initial attack, while Inq, B, T and Bc-h would degrade PHN metabolites. The predicted roles were further confirmed by physiological, RT-qPCR and metaproteomic assays. SC-1 with AM as the sole PHN degrader was the most efficient. The ecological roles inferred in this study can be applied to optimize the design of bacterial consortia and tackle the biodegradation of complex environmental pollutants.